Impact Experiential Marketing On Customer Satisfaction Through Experiential Value As Intervening Variables In Users Xiaomi Smartphone In The Padang City (JURNAL ECONOMICA : Research of Economic And Economic Education, 2020)
This study aims to prove the effect of experiential marketing on customer satisfaction through experiential value as an intervening variable. In this research 150 consumers used the Xiaomi smartphone with various types. The sampling method used was accidental sampling while the analytical tool to prove the truth of the hypothesis was done using the Structural Equaiton Model (SEM) which was processed through Smart PLS. Based on the results of hypothesis testing found that experiential marketing has a positive effect on customer satisfaction but experiential marketing has no effect on customer satisfaction after going through experiential value of Xiaomi smartphone users in Padang.